We're to graph y=-2x+1

7 answers

To graph the equation y = -2x + 1, we can start by plotting a few points and then connecting them to form a line.

We can choose any values for x and substitute them into the equation to find the corresponding y-values. Let's choose x = -2, 0, and 2.

When x = -2:
y = -2(-2) + 1
y = 4 + 1
y = 5

So the first point is (-2, 5).

When x = 0:
y = -2(0) + 1
y = 1

So the second point is (0, 1).

When x = 2:
y = -2(2) + 1
y = -4 + 1
y = -3

So the third point is (2, -3).

Now, we can plot these points on a graph and connect them with a straight line.

Here is what the graph looks like:

|
5 | *
|
|
1 |
|
|
-3 | *
----------------------------------------
-4 -2 0 2 4 6 8

The line passes through the points (-2, 5), (0, 1), and (2, -3) and extends indefinitely in both directions.
Only two dots
Apologies for the confusion. To graph the equation y = -2x + 1, we need to plot two points and connect them to form a line.

Let's choose x = 0 and x = 1:

When x = 0:
y = -2(0) + 1
y = 0 + 1
y = 1

So the first point is (0, 1).

When x = 1:
y = -2(1) + 1
y = -2 + 1
y = -1

So the second point is (1, -1).

Now, we can plot these points on a graph and connect them with a straight line.

Here is what the graph looks like:

|
| *
|
|
|
| *
-------------------------
-1 0 1 2

The line passes through the points (0, 1) and (1, -1) and extends indefinitely in both directions.
How to graph y=3x-4
To graph the equation y = 3x - 4, we can follow a similar process as before by plotting points and connecting them to form a line.

Let's choose x = -2, 0, and 2:

When x = -2:
y = 3(-2) - 4
y = -6 - 4
y = -10

So the first point is (-2, -10).

When x = 0:
y = 3(0) - 4
y = 0 - 4
y = -4

So the second point is (0, -4).

When x = 2:
y = 3(2) - 4
y = 6 - 4
y = 2

So the third point is (2, 2).

Now, we can plot these points on a graph and connect them with a straight line.

Here is what the graph looks like:

|
-10| *
|
|
-4| *
|
|
2| *
-------------------------
-2 0 2 4

The line passes through the points (-2, -10), (0, -4), and (2, 2) and extends indefinitely in both directions.
Two dots
Apologies for the confusion. To graph the equation y = 3x - 4, we need to plot two points and connect them to form a line.

Let's choose x = 0 and x = 1:

When x = 0:
y = 3(0) - 4
y = 0 - 4
y = -4

So the first point is (0, -4).

When x = 1:
y = 3(1) - 4
y = 3 - 4
y = -1

So the second point is (1, -1).

Now, we can plot these points on a graph and connect them with a straight line.

Here is what the graph looks like:

|
-4 | *
|
|
-1 | *
|
|
-------------------------
-2 0 2 4

The line passes through the points (0, -4) and (1, -1) and extends indefinitely in both directions.